Effect of Laparoscopic Pancreaticoduodenectomy in Elderly People: A Meta-analysis. Issue 8 (September 2021) - Zhang, Wei; Huang, Zhangkan; Zhang, Jianwei; Che, Xu
Abstract : Supplemental digital content is available in the text. Abstract: Pancreaticoduodenectomy is considered to be the most complicated operation in abdominal surgery. The purpose of this study was to evaluate the safety and efficacy of laparoscopic pancreaticoduodenectomy (LPD) in elderly patients. We searched PubMed, Embase, and Cochrane Library databases for relevant studies that were published before June 2020. Seven cohort studies were eligible with 3200 patients. The result of meta-analysis showed that, for the elderly, severe complications, clinical pancreas fistula, and delayed gastric emptying in the LPD group were significantly lower than those in the open pancreaticoduodenectomy (OPD) group. There was no significant difference in postoperative bleeding, reoperation, and readmission between the 2 groups. For the LPD, the mortality, delayed gastric emptying, and severe complication in elder patients were significantly higher than those in young patients. There was no significant difference in postoperative bleeding, R0 rate, reoperation rate, and readmission rate between the aged and the young. Therefore, LPD can reduce postoperative complications in elderly patients compared with OPD, which can be used as a potential alternative to OPD in elderly patients. However, laparoscopic approach cannot eliminate the high risk of postoperative death and severe complications caused by age. More high-quality studies need to be done for further verification.